2022
DOI: 10.3389/fped.2021.746437
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sweeteners Intake Modulates Gut Microbiota and Exacerbates Learning and Memory Processes in Adult Male Offspring

Abstract: Background: There is increasing evidence that gut microbiota in offspring is derived in part from maternal environment such as diet. Thus, sweeteners intake including caloric or non-caloric during perinatal period can induce gut dysbiosis and program the offspring to develop cognitive problems later in life.Objective: To determine the effect of maternal high-sweeteners intake during gestation and lactation on gut microbiota shifts in adult male offspring rats and the impact on cognitive dysfunction.Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…Our ndings showed slight modi cations in gut microbiota composition after NNS exposure, especially in the interaction between HFD and sucralose supplementation. Modi cations in gut microbiota without alterations in glycemic or energy metabolism after natural or arti cial NNS exposure were reported in previous studies in healthy or with obesity-induced animals [12,13,43]. The lack of pronounced NNS effects on gut microbiota in our study differs from previous research using model animals which have been administered sucralose or reb A at no realistic doses even with chronic consumption (100 and 10 times the ADI, respectively) [10,11,21].…”
Section: Discussioncontrasting
confidence: 91%
“…Our ndings showed slight modi cations in gut microbiota composition after NNS exposure, especially in the interaction between HFD and sucralose supplementation. Modi cations in gut microbiota without alterations in glycemic or energy metabolism after natural or arti cial NNS exposure were reported in previous studies in healthy or with obesity-induced animals [12,13,43]. The lack of pronounced NNS effects on gut microbiota in our study differs from previous research using model animals which have been administered sucralose or reb A at no realistic doses even with chronic consumption (100 and 10 times the ADI, respectively) [10,11,21].…”
Section: Discussioncontrasting
confidence: 91%
“…Amplicon size was analyzed via 3% agarose gel electrophoresis (PowerPac, Bio-Rad, Hercules, CA, USA) and amplicons were purified using AMPure XP. The indices of the Nextera XT kit were added via new PCR, following Illumina’s protocol [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Given that the gut-brain axis plays a crucial role in the etiology of mental illness and cognitive and memory disorders, de la Garza et al indicated that maternal gut dysbiosis deteriorates learning procedures and leads to memory loss susceptibility in adult male offspring rats. A maternal high-stevia diet induced the upregulation of Bacteroidales and Clostridiales, leading to memory loss and cognitive problems in offspring lasting up to adulthood, while the changes found in these phyla were independent of their body weight gain [41]. A summary of the above discussed studies is shown in Table 2.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…More specifically, alpha diversity is defined as "the average species diversity in a particular area or habitat", and beta diversity as "the diversity of species between two habitats or the measure of similarity or dissimilarity of two regions" [42]. In our review, we detected eight studies measuring alpha diversity, using a variety of different indices (Shannon index, Simpson index, Pielou's evenness, Operational Taxonomic Units, Chao1 richness, and Faith's Phylogenetic Diversity Index) [27,29,34,35,[37][38][39]41]. Further-more, we identified three studies evaluating beta diversity [34,38,39] (Table 3).…”
Section: The Effects Of Stevia and Steviol Glycosides On Microbial Di...mentioning
confidence: 99%